Cooperative Learning Approach for enhancing Emotional Intelligence, Problem Solving Ability and Scientific Creativity among Secondary School Students - Jeena K. G. (Voices of Teachers and Teacher Educators, 2023)
Cooperative learning approach helps to develop the skills of working together, sharing ideas and respecting the views of other students. This study aimed to examine the effectiveness of the cooperative learning approach on secondary school students’ emotional intelligence, problem solving ability and scientific creativity. The experimental study design adopted for the study was post-test non-equivalent experimental control group design using a sample of 60 students. Statistical techniques used were descriptive statistics and inferential statistics through two-way ANOVA. The major findings revealed that the students, who learned through cooperative learning approach enhanced their emotional intelligence, problem solving ability and scientific creativity. The results of the research motivate teachers to rethink their teaching strategies and redefine their approaches toward science teaching and learning. When scientific concepts are transacted through cooperative learning approach, the learning becomes joyful and it helps to attain the concept more clearly besides enhancing their creativity, leadership skills, cooperation, tolerance and overall achievement.